Determination of the Prevalence and Economic Importance of Bee Parasitic Diseases in Devrekani District of Kastamonu Province - Burak ŞAHİN; Burak ÖMEROĞLU; Melek KORKMAZ; Hümeyra ÖZGEN; Tuğba Nur EREN (ISPEC Journal of Agricultural Sciences)
Beekeeping activities, widely carried out around the world, hold significant importance in our country due to its rich vegetation and climate characteristics. There are parasitic, bacterial, viral, and fungal diseases that are crucial in beekeeping. Parasitic infestations such as Nosemosis, Varroasis, Aethina tumida, Tropiaelaps spp., and Acarapis woodi are notable among bee parasites. However, when reviewing the literature, it was noted that there are insufficient studies on bee parasitic diseases. Furthermore, there are no studies on bee parasitic diseases in the Devrekani district. The primary source of income for the people living in the Devrekâni district, where the study took place, is animal husbandry and agriculture. The aim of the study is to determine the prevalence and seasonal distribution of bee parasitic diseases in the Devrekani district, to provide information to beekeepers about bee farming, to identify ways to protect against diseases observed in bees, to minimize veterinary health costs with the precautions to be taken, and to prevent the spread of bee parasitic diseases seen in the district to neighboring provinces through migratory beekeeping. Additionally, the aim is to determine the economic loss due to the decrease in honey sales resulting from hive deaths due to parasitic diseases and the cost of establishing new hives. The research material consisted of samples suspected of parasitic diseases taken from 21 different beekeeping enterprises registered with the Devrekani District Directorate of Agriculture between May 2023 and January 2024. Samples were collected from the hives and placed in sterile sample bags. Diagnosis of samples suspected of parasitic diseases was conducted in the parasitology laboratory using a Nikon brand SMZ 745T model stereo microscope and NIS Elements-D software imaging program. As a result of the diagnosis, no bee parasitic diseases were found. The absence of bee parasitic diseases indicates the possibility of bee deaths due to bacterial, fungal, and viral diseases, and suggests that multidisciplinary studies can be conducted on this issue.